Implementasi Pembelajaran PAI Moderasi Beragama Melalui Kegiatan Isra’ Mi’raj dan Peringatan Natal di SMAN 2 Tuban - Riswanda Arneta Pratiwi; Umu Fahiimah; Roro Kusuma Dwi Nur Ma’rifati (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine the implementation of Islamic Religious Education (PAI) learning based on religious moderation through the commemoration of Isra’ Mi’raj and the celebration of Christmas at SMAN 2 Tuban. The research applies a descriptive qualitative approach conducted in a public senior high school with students from diverse religious backgrounds. Primary data were collected through interviews with the Head of OSIS and the Head of ROHIS, while additional data were obtained from documentation and literature review. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out using an interactive model consisting of data processing, data presentation, and conclusion drawing. The results indicate that the implementation of religious moderation in PAI learning is manifested through inclusive and educative religious activities. The commemoration of Isra’ Mi’raj strengthens spiritual values and fosters attitudes of tawassuth (moderation), tasamuh (tolerance), and tawazun (balance). On the other hand, the Christmas celebration provides opportunities for Christian and Catholic students to worship according to their beliefs, while simultaneously encouraging mutual respect among students from different religious backgrounds. The internalization process occurs through cognitive, affective, and behavioral aspects supported by school culture and teachers’ role modeling. This study contributes to the development of relevant religious moderation practices in educational institutions and emphasizes the importance of sustainable habituation in shaping tolerant student character.   Keywords: Religious Moderation, Islamic Religious Education, Christmas Celebration, Tolerance, Isra’ Mi’raj